Romans and others in the Work of Rutilius Namatianus - Boch, Viviana (De Rebus Antiquis, 2020)
This work seeks to interpret the fundamental ideas that gave meaning to the poem by Claudius Rutilius Namatianus and vision of those who watched as alien to their mentality, pressing urgent moments for the life of the Late Roman Empire. Although his work has been thoroughly analyzed it is considered appropriate to make a new critical reading of it that allows finding relationships, proximity and differences with the findings and arguments of Quintus Aurelius Symmachus.